1998
DOI: 10.1016/s0735-1097(98)00310-6
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in potential arterial switch candidates with transposition of the great arteries

Abstract: Of those neonates admitted with TGA, 4.1% died before surgery. Eleven of 12 (3.7%) died due to consequences of inadequate interatrial mixing despite PGE1 infusion. Earlier diagnosis and BAS are critically important in determining survival. Early ASO may improve survival in patients weighing <2 kg. Prenatal diagnosis with delivery in a high-risk obstetrical unit with facilities for immediate BAS and supportive therapy for pulmonary hypertension and ventricular failure may be necessary to salvage this group of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 16 publications
1
55
0
2
Order By: Relevance
“…Both a multi-institutional prospective study and an institutional retrospective study at The Hospital for Sick Children, Toronto, suggested that as many as 4% of neonates with TGA die before repair. 6,11 One problem with ascertaining the number of infants with TGA and the lethal combination of restrictive foramen ovale and ductal constriction is that the neonate may die before a diagnosis of TGA is made and referral to a tertiary care center can be arranged. In fact, a further review of autopsy records at The Hospital for Sick Children in the past 10 years identified 2 more cases of very early death after delivery at outside hospitals with TGA, and autopsy confirmed the presence of ductus arteriosus and foramen ovale restriction.…”
Section: Prediction Of Early Neonatal Death In Tgamentioning
confidence: 99%
“…Both a multi-institutional prospective study and an institutional retrospective study at The Hospital for Sick Children, Toronto, suggested that as many as 4% of neonates with TGA die before repair. 6,11 One problem with ascertaining the number of infants with TGA and the lethal combination of restrictive foramen ovale and ductal constriction is that the neonate may die before a diagnosis of TGA is made and referral to a tertiary care center can be arranged. In fact, a further review of autopsy records at The Hospital for Sick Children in the past 10 years identified 2 more cases of very early death after delivery at outside hospitals with TGA, and autopsy confirmed the presence of ductus arteriosus and foramen ovale restriction.…”
Section: Prediction Of Early Neonatal Death In Tgamentioning
confidence: 99%
“…With the introduction of the arterial switch operation in Toronto, only Ϸ4% of babies now die before the arterial switch procedure, and for simple transposition the surgical mortality is Ͻ2%. 102 What a profound change from the observations of Liebman, Cullum, and Belloc, who addressed the "natural" history of patients with transposition of the great arteries in the era before balloon atrial septostomy and Mustard repair. 103 This is but one of the remarkable sagas in congenital heart disease.…”
Section: Freedom Et Al Pediatric Cardiology and CV Surgery Iv-61mentioning
confidence: 99%
“…[1][2][3][4] Of those neonates admitted with TGA, mortality is estimated around 4% and is mostly due to inadequate interatrial mixing despite prostaglandin E1 infusion. 5 We have previously reported that prenatal diagnosis of TGA reduced neonatal mortality and morbidity. 3 However, early demise of neonates with TGA has been reported even after a prenatal diagnosis, suggesting that there was no site available for mixing immediately after birth.…”
mentioning
confidence: 94%
“…3 However, early demise of neonates with TGA has been reported even after a prenatal diagnosis, suggesting that there was no site available for mixing immediately after birth. 3,[5][6][7][8] Indeed, antenatal restriction of the foramen ovale and/or the ductus arteriosus were found predictive of significant neonatal morbidity and mortality. 9 Because the surgical mortality for the arterial switch operation is as low as 2% in many institutions, 10 -13 the preoperative mortality is a major issue in the management and outcome of infants with TGA.…”
mentioning
confidence: 99%